Horizon: Balancing TCP over Multiple Paths in Wireless Mesh Network - Radunovic, Bozidar; Gkantsidis, Christos; Gunawardena, Dinan; Key, Peter (Association for Computing Machinery, Inc., 2008)
There has been extensive work on network architectures that support multi-path routing to improve performance in wireless mesh networks. However, previous work uses ad-hoc design principles that cannot guarantee any network-wide performance objectives such as conjointly maximizing resource utilization and improving fairness. In parallel, numerous theoretical results have addressed the issue of optimizing a combined metric of network utilization and fairness using techniques based on back-pressure scheduling, routing and flow control. However, the proposed theoretical algorithms are extremely difficult to implement in practice, especially in the presence of the 802.11 MAC and TCP. We propose Horizon, a novel system design for multi-path forwarding in wireless meshes, based on the theoretical results on back-pressure. Our design works with an unmodified TCP stack and on top of the existing 802.11 MAC. We modified the backpressure approach to obtain a simple 802.11-compatible packetforwarding heuristic and a
MobiCom'08